Changes in the prevalence and trends of female genital mutilation in Iraqi Kurdistan Region between 2011 and 2018 - Nazar P. Shabila (BMC, 2021)
Abstract Background Female genital mutilation (FGM) is commonly practiced in Iraqi Kurdistan Region, where there are extensive efforts to combat the practice over the last decade. This study aimed to determine the trends and changes in the FGM prevalence in Iraq between 2011 and 2018 and assess their associated factors. Methods Secondary data analysis of the Iraq Multiple Indicator Cluster Survey 2011 and 2018 was carried out to calculate the prevalence and the relative changes in the prevalence of FGM for 2011 and 2018 by governorate. The change in the prevalence was compared with the changes in other exposure variables such as age, education level, wealth, and area of residence over the same period. Results The prevalence of FGM in 2018 was high in Erbil and Suleimaniya governorates (50.1% and 45.1%). The prevalence of FGM decreased remarkably from 2011 to 2018 in all governorates of the Iraqi Kurdistan Region. The decrease in the prevalence was statistically significant in Erbil and Suleimaniya. FGM prevalence declined remarkably in all age, education level, residence area groups, and most economic level groups. Such decline was associated with a significant increase in the education level, wealth, and urban residence. The decline was highest in the younger age groups, with a relative change of − 43.0% among 20-24 years and − 39.2% among 15-19 years. The decline was also highest in those with secondary and higher education (relative change = −32%). The decline was higher in rural areas than in urban areas (relative change = −35.3% and − 27.4%, respectively). The decline was higher among the poorest and second wealth quintile (relative change = −38.8% and − 27.2%, respectively). Conclusion The trend of FGM in Iraqi Kurdistan Region declined remarkably and significantly from 2011 to 2018. Further decline is predicted because of having lower rates and a higher decline in the younger age groups. However, the rates remained high in Erbil and Suleimaniya governorates that need further intensifying the preventive measures. The education level of women plays a primary role in decreasing the prevalence and should be considered in future efforts to ban the practice.